2022
DOI: 10.1002/ptr.7577
|View full text |Cite
|
Sign up to set email alerts
|

Xanthotoxin (8‐methoxypsoralen): A review of its chemistry, pharmacology, pharmacokinetics, and toxicity

Abstract: Xanthotoxin (XAT) is a natural furanocoumarins, a bioactive psoralen isolated from the fruit of the Rutaceae plant Pepper, which has received increasing attention in recent years due to its wide source and low cost. By collecting and compiling literature on XAT, the results show that XAT exhibits significant activity in the treatment of various diseases, including neuroprotection, skin repair, osteoprotection, organ protection, anticancer, antiinflammatory, antioxidative stress and antibacterial. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 200 publications
0
7
0
Order By: Relevance
“…Regarding the bioactive properties of lovage coumarins, apterin has been previously determined to be a common apiaceous coumarin [ 65 ] and showed antioxidant [ 66 ], anti-tumor [ 67 ], anticholinesterase [ 68 ], antidiabetic [ 69 , 70 ], and anti-inflammatory activities [ 71 ]. Xanthotoxin has demonstrated various bioactivities, such as anticancer, anti-inflammatory, antioxidative stress and antibacterial activities [ 72 ], while pimpinellin was determined to be an effective preventer of platelet-related thromboembolic diseases (such as atherosclerosis [ 73 ]), and isopimpinellin is antibacterial agent against methicillin-resistant Staphylococcus aureus [ 74 ]. Thus, lovage roots are a valuable source of bioactive coumarins.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the bioactive properties of lovage coumarins, apterin has been previously determined to be a common apiaceous coumarin [ 65 ] and showed antioxidant [ 66 ], anti-tumor [ 67 ], anticholinesterase [ 68 ], antidiabetic [ 69 , 70 ], and anti-inflammatory activities [ 71 ]. Xanthotoxin has demonstrated various bioactivities, such as anticancer, anti-inflammatory, antioxidative stress and antibacterial activities [ 72 ], while pimpinellin was determined to be an effective preventer of platelet-related thromboembolic diseases (such as atherosclerosis [ 73 ]), and isopimpinellin is antibacterial agent against methicillin-resistant Staphylococcus aureus [ 74 ]. Thus, lovage roots are a valuable source of bioactive coumarins.…”
Section: Resultsmentioning
confidence: 99%
“…They measured the concentration of XAT ( 190 ) in plasma by UPLC-MS and found that XAT( 190 ) was rapidly absorbed after oral administration of XAT ( 190) , with T max of about 55 min and T 1/2 of about 90 min. 88…”
Section: Pharmacokinetics Studiesmentioning
confidence: 99%
“…rate ofXAT (190) is very low, and the absolute bioavailability of XAT (190) in rat plasma after oral administration is less than 1%. They measured the concentration of XAT (190) in plasma by UPLC-MS and found that XAT(190) was rapidly absorbed after oral administration of XAT (190), with T max of about 55 min and T 1/2 of about 90 min 88. …”
mentioning
confidence: 99%
“…It has also been shown that the pro-apoptotic activity of the compound is related to its ability to inhibit PI3K kinase activity in MCF-7 and ZR-75 breast cancer cells [10][11][12]. In the case of the bergapten isomer-xanthotoxin-the induction of apoptosis in HepG2 cells is associated with the inhibition of survival signals through the intracellular RAS-RAF-MEK-ERK pathway [13,14]. Another furanocoumarin with defined biological activity is imperatorin.…”
Section: Introductionmentioning
confidence: 99%